Cotula australis (Sieb. ex Spreng.) Hook. f. - a New Record for the North-western and Eastern Himalayas - Vaid, K. M.; Naithani, H. B. (Indian Forester, 1970)
Cotula australis (Sieb. ex Spreng.) Hook. f., a Compositae, native of Australia and New Zealand, hitherto recorded from the South Indian hill stations only is now reported to be naturalizing wet places in the Himalayas, presently in Kulu, Simla and Darjeeling. It appears to be a recent introduction in the Himalayan region, possibly, having come as an admixture with the imported foodgrains or even through sheep imported as breeding stock from Australia.